Climate change, in the framework of the Constructal Law - Clausse, Marc (2012)
Here we present a simple and transparent alternative to the complex models of earth’s thermal behaviour under time-changing conditions. We show the one-to-one relationship between changes in atmospheric properties and time-dependent changes in temperature and its distribution on earth. The model accounts for convection and radiation, thermal inertia and changes in albedo (ρ) and greenhouse factor (γ). The constructal law is used as the principle that governs the evolution of fl ow confi guration on earth. The model showed that for two time-dependent scenarios, (δρ = 0.002; δγ = 0.011) and (δρ = 0.002; δγ = 0.005) the predicted equatorial and polar temperature increases and the time scales are (ΔTH = 1.16 K; ΔTL = 1.11 K; 104 years) and (0.41 K;0.41 K; 57 years), respectively. A continuous model of temperature variation was used to predict the thermal response of the Earth’s surface to changes bounded by δρ = δγ and δρ = −δγ. The poleward heat current reaches its maximum in the vicinity of 35° latitude,accounting for the position of the Ferrel cell between the Hadley and Polar Cells.